Agonist-dependent mechanism of Mu-opioid receptor desensitization. - Chu, Ji (My University, 2009)
Desensitization of the μ-opioid receptor (MOR) has been implicated as an important regulatory process in the development of tolerance to opiates. Desensitization of G-protein coupled receptor (GPCR) is thought to involve receptor phosphorylation and subsequent recruitment of βArrestins (βArrs). However, the roles of receptor phosphorylation and βArr in morphine-induced MOR desensitization remain to be demonstrated; this may result from the insensitivity of the methods used to study receptor function. Using MOR-induced intracellular Ca2+ ([Ca2+]i) release to monitor receptor activation, [D-Ala2, N-Me-Phe4, Gly5-ol]-enkephalin (DAMGO) induced MOR desensitization in a receptor phosphorylation- and βArr-dependent manner. DAMGOinduced desensitization was blunted in HEK293 cells expressing the MORS375A mutant and was eliminated in MEF cells isolated from βArr2 knockout mice expressing the wild type MOR. However, although morphine induced a more rapid desensitization of [Ca2+]i release than DAMGO did and could induce the phosphorylation of the Ser375 residue of MOR, morphine-induced desensitization was not influenced by mutating MOR phosphorylation sites or in MEF cells lacking βArr1 and 2. In contrast, morphine induced MOR desensitization via protein kinase C (PKC). By using subtype-specific inhibitors, PKCε was shown to be the PKC subtype activated by morphine and the subtype responsible for morphine-induced desensitization. Meanwhile, DAMGO did not increase PKCε activity and DAMGO-induced MOR desensitization was not affected by a PKCε inhibitor. Among the various proteins within the receptor signaling complex, Gαi2 was phosphorylated by morphine-activated PKCε. Moreover, mutating v three putative PKC phosphorylation sites, Ser44, Ser144 and Ser302 on Gαi2 to Ala attenuated morphine-induced, but not DAMGO-induced desensitization. In addition, pretreatment with morphine desensitized cannabinoid receptor CB1 agonist WIN 55212-2-induced [Ca2+]i release, and this desensitization could be reversed by pretreating with a PKCε inhibitor or overexpressing of Gαi2 with the putative PKC phosphorylation sites mutated. Thus, depending on the agonist, activation of MOR could lead to heterologous desensitization and probable crosstalk between MOR and other Gαi-coupled receptors such as the CB1 receptor.
University of Minnesota Ph.D. dissertation. December 2009. Major: Pharmacology. Advisor: Dr. Ping-Yee Law. 1 computer file (PD); xiii 178 pages. Ill. (some col.)
Keywords: Agonist-dependent; Desensitization; G protein-coupled receptor; Opioid receptor; Pharmacology